Functional characterization and salt-stress-induced expression analysis of soybean GMCYP86A1S genes (Bangladesh Journal of Botany, 2025)
This study cloned the homologous genes (GmCYP86A1a and GmCYP86A1b) of AtCYP86A1 in soybean by homology comparison. Subsequently, systematic analyses of the gene structures, regulatory elements in promoter sequences, and physicochemical properties of GmCYP86A1a and GmCYP86A1b were conducted using bioinformatics approaches. Additionally, quantitative assessment of the expression patterns of these two genes and their transcriptional responses to NaCl stress was performed via qRT-PCR assays. The experimental evidence demonstrated that GmCYP86A1a and GmCYP86A1b exhibit highly similar gene structures, and both encode proteins harboring characteristic structural motifs typical of CYP450 enzymes. The promoter regions of the GmCYP86A1a and GmCYP86A1b genes contain diverse cis-acting elements that regulate growth and development, mediate phytohormonal signaling, and coordinate environmental stress adaptation mechanisms. The physicochemical properties of GmCYP86A1a and GmCYP86A1b proteins show distinct differences, both proteins are localized on the endoplasmic reticulum. Furthermore, GmCYP86A1a and GmCYP86A1b are root-specific genes and are induced and upregulated under NaCl stress. The current findings establish a framework for further investigation of molecular mechanisms by which GmCYP86A1a and GmCYP86A1b genes mediate salt stress adaptation in soybean.Bangladesh J. Bot. 54(3): 721-729, 2025 (September) Special